Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Konsumen Di Alfamart Cayur Kresek Tangerang - Nazwirman Nazwirman; Efendy Zain (Journal of Economics and Business Aseanomics (JEBA), 2018)
Research that aims to analyze and Strengthen Promotion Variables and Service Quality to Consumer Loyalty in Alfamart Cayur Kresek Tangerang District. Quantitative research methods. The number of samples is 155 respondents and the analysis used is SPSS 23. The results obtained by regression equation Y = 0,543 + 0,221X1 + 0,633X2. Partial t test shows promotion and quality of service to consumer loyalty. F-Test Results Promotion and Service Quality together to Consumer Loyalty. Value (RÂ²) of 0,558 or 57,6 percent which mean variable ability X1 and X2 in explain variable Y equal to 57,6 percent.